Influence of using animated video media in online learning at junior high school - Risma Rizqiana Haq; Lies Diana Dwi Irawati (Curricula: Journal of Curriculum Development, 2022)
Learning is an activity that combines various things, namely humans, facilities, and procedures so that all parties are related to one another to achieve a goal. The facilities include learning media, including animated video media used in online learning during the COVID-19 pandemic. This research aims to see the influence and effectiveness of animated video media in online learning. This research uses a quantitative approach with descriptive methods. The study results show that animated videos can improve the quality of the learning process; the material presented using animated media becomes more straightforward and more accurate, so students understand the material more easily. The obstacle is online access to watch or download animated videos. Therefore, it can be concluded that animated video media is effectively used as a learning medium for distance or online learning.